THE RUSSO-GEORGIAN FIVE-DAY WAR: THE PRICE TO BE PAID AND ITS UNINTENDED CONSEQUENCES - KAKACHIA, Kornely (CENTRAL ASIA AND THE CAUCASUS, 2009)
The dissolution of empires is frequently violent, and the breakup of the Soviet Union was no exception. The collapse of the U.S.S.R. was marked by ethnically-based violence, especially in the Southern Caucasus. Since its independence, Georgia has been the most vocally independent-minded country in the former Soviet Union. As Georgia’s ambitions to draw close to Europe and the transat-lantic community became clearer, its relations with Russia deteriorated. After the Rose Revolution relations between Georgia and Russia remain problematic due to Russia’s continuing political, economic and military support to separatist governments in Abkhazia and South Ossetia. In recent years, Moscow granted the majority of Abkhaz and South Ossetians Russian citizenship and moved to establish close economic and bureaucratic ties with the two separatist republics, effectively enacting a creeping annexation of both territories. Use of Russian citizenship to cre-ate a “protected” population residing in a neighboring state to undermine its sovereignty is a slippery slope that is now leading to a redrawing of the former Soviet borders. Russia’s recent attack on Georgia followed several years of provocative acts engineered in Moscow to destabilize Georgia. In the summer of 2006, tension increased between Tbilisi and Mos-cow. The Georgian government conducted a police operation to eliminate organized criminal groups operating in the Upper Kodori Valley region of Abkhazia, which restored the rule of law and the government’s authority over this portion of its sovereign territory. Georgia later arrested several Russian military intelligence officers it accused of conducting bombings in Gori. Moscow responded with a vengeance, closing Russia’s only road crossing with Georgia, suspending air and mail links, imposing embargoes against exports of Georgian wine, mineral water, and agricultural goods, and even rounding up people living in Russia (including school children) with ethnic Georgian names and deporting them.1 At least two Georgians died during the deportation process.2